The Origin of the Alphabet - Tur-Sinai, N. H.
1. The Problem — 2. The Letters and the Meaning of Their Names — 3. The Early "Canaanitic Alphabet" — 4 . The Didactic Tradition of Word-Sequences Representing the Letters of the Alphabet.